NEUROFUNCTIONAL DEFICITS DURING DECISION-MAKING AND AFFECTIVE PROCESSING IN CHRONIC MARIJUANA USERS - Wesley, Michael John (Wake Forest University, 2010)
Marijuana is the most frequently used illegal drug in the country with medicinal and recreational use increasing. The present series of studies was designed to examine functional brain activity associated with altered decision-making and affective or emotional processing in long-term chronic marijuana users (MJ Users).
Keywords: Brain Activity; Cannabis; fMRI; Human; International Affective Picture System; Iowa Gambling Task